Información General: Grupo de Investigación en Informática - Universidad de Los Andes (SABER ULA, 2006)
Lines of Research: - Development of educational software for mathematics and physics - Modeling and simulation of engineering processes. - Mathematics.
Keywords: Grupo de Investigación en Informática; Desarrollo de software educativo para matemáticas y física; Modelado y simulación de procesos en ingeniería; Matemática pura; Matemáticas; Ingeniería; Ciencias Computacionales; Núcleo Táchira (NUTULA); Núcleo Táchira (NUTULA); Development of educational software for mathematics and physics; Modeling and simulation of engineering processes; Mathematics; Grupo de Investigación; Mathematics; Computational Sciences; Engineering; Unidades de investigación